1999
DOI: 10.1002/(sici)1097-4598(199904)22:4<473::aid-mus8>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart involvement in muscular dystrophies due to sarcoglycan gene mutations

Abstract: Mutations in the sarcoglycan genes cause autosomal‐recessive muscular dystrophies. Because sarcoglycan genes and their protein products are highly expressed both in skeletal and cardiac muscle, patients with these mutations might be expected to be at risk to develop dilated cardiomyopathy. We therefore studied 13 patients with α‐, β‐, γ‐sarcoglycan gene mutations by thorough cardiological assessment. Electrocardiographic or echocardiographic abnormalities were observed in about 30% of cases showing a severe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 35 publications
1
57
0
4
Order By: Relevance
“…Using animal models and virus-gene transfer techniques, it has been demonstrated that genetic deficiencies of the SG complex can be corrected in vivo Durbeej et al 2003). Inherited cardiomyopathy can be associated with genetic defects in the DGC (Towbin 1998), and a correlation between the primary mutation of the SG gene and cardiomyopathy has been established (Melacini et al 1999). Accordingly, the genetically engineered models of b-SG and d-SG-null mice developed cardiomyopathy (Coral-Vasquez et al 1999;Durbeej et al 2000).…”
Section: Dgc and Muscular Dystrophymentioning
confidence: 99%
“…Using animal models and virus-gene transfer techniques, it has been demonstrated that genetic deficiencies of the SG complex can be corrected in vivo Durbeej et al 2003). Inherited cardiomyopathy can be associated with genetic defects in the DGC (Towbin 1998), and a correlation between the primary mutation of the SG gene and cardiomyopathy has been established (Melacini et al 1999). Accordingly, the genetically engineered models of b-SG and d-SG-null mice developed cardiomyopathy (Coral-Vasquez et al 1999;Durbeej et al 2000).…”
Section: Dgc and Muscular Dystrophymentioning
confidence: 99%
“…Genetic defects of sarcoglycans, dystroglycan, and/or dystrophin are believed to play an important role in the development of muscular diseases such as cardiomyopathy and muscular dystrophies (6,7,29,30). However, whether or not there is a substantial contribution of alterations in the DRGP complex of the heart without genetic mutation to the development of heart failure remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Inherent mutation or depletion of sarcoglycans and/or dystrophin genes causes muscular dystrophy and dilated cardiomyopathy in humans and hamsters (6,7). Recent studies have shown that δ-sarcoglycan gene transfection mediated by adeno-associated virus improves cardiac function, sarcolemmal stability, and survival of TO-2 hamsters (8), which are an animal model mimicking human dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Conduction defects have been evidenced in Duchenne muscular dystrophy [41,42], Becker muscular dystrophy [43,44], myotonic dystrophy type 1 and 2 [45,46], Emery-Dreifuss muscular dystrophy [47], and limb girdle muscular dystrophy [48,49].…”
Section: Pkcs and Muscular Dystrophiesmentioning
confidence: 99%